From Plan To Reality: Rencana Pelaksanaan Pembelajaran Serta Pengaruhnya Terhadap Kualitas Pembelajaran Akuntansi di SMK dan SMA Se Kota Gorontalo - Podungge, Rahmawati; Hafid, Radia; Mahmud, Melizubaida; Panigoro, Meyko; Koniyo, Rierind (Gorontalo State University, 2026)
ABTRACTThis study aims to determine the effect of the Lesson Plan on the quality of Accounting learning in vocational and senior high schools in Gorontalo City. The approach used is quantitative with primary data obtained through questionnaires distributed to vocational and senior high school teachers. The sample size of the study was 40 respondents. The data analysis technique used simple linear regression. The results of the study indicate that the Lesson Plan has a significant effect on the quality of Accounting learning. The coefficient of determination value of 65 percent indicates that the quality of learning can be explained by the Lesson Plan variable, while the remaining 35 percent is influenced by other variables not examined. The conclusion of this study confirms that teachers need to maximize the implementation of the Lesson Plan. The Lesson Plan serves as a guideline that structures the learning process so that teachers are more systematic, directed, and effective. The implementation of a good Lesson Plan encourages planned, interactive, and student-centered learning, thus impacting the improvement of the quality of learning and learning outcomes in Accounting in senior high schools.